Komparasi Kebijakan Pengelolaan Limbah Medis Covid-19 Di Indonesia Dan Malaysia - Vivi Elvina panjaitan (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2021)
There are still many developing countries that have not managed Covid-19 medical waste properly and effectively even though the current amount of Covid-19 medical waste production is very worrying. Therefore, the author analyze and compare the Covid-19 medical waste management policies that were formulated and implemented in Indonesia and Malaysia. Different policies and implementations in Malaysia using as recommendations and other recommendations from author. This research method is comparative descriptive with qualitative approach and uses secondary data. The results of the literature study that the Covid-19 medical waste management policies in Indonesia and Malaysia weren’t much different. Each country has a policy strategy that was formulated before the Covid-19 pandemic occurred, namely PP No. 101 Tahun 2014 in Indonesia and Environmental Quality Act 1974 in Malaysia. Each country describes these policies into operational Covid-19 medical waste management policies. In implementation and monitoring, Indonesia has similarities as well as differences with Malaysia. The similarities are the government collaborates with several agencies and private sector in managing Covid-19 medical waste, the government socializes the Covid-19 medical waste management policies, conducts inspections, provides complaint services. The differences are the Indonesian government conducts a coaching clinic, prepares environmental extension functions, private sector that are still taking care of permits may operate. In Malaysia, there are seven private sector that have permits to manage Covid-19 medical waste, using robots to help manage Covid-19 medical waste, imposing fines and imprisonment for violators, providing Electronic Scheduled Waste Management Application. The strategy taken by Malaysian government can be used as recommendations in managing Covid-19 medical waste. The other recommendations are the government educates the public up to the RT and RW levels by involving village apparatus, religious leaders, youth organizations, using the recrystallization method, using Covid-19 medical waste transport vehicle equipped with a GPS and barcode systems.